The haunting of Emily Grace - Taylor, Elena (Severn House, 2025)
"Drowning in grief, Emily Grace has lost everything: her home, her friends, her career. Only one lifeline remains--a job working for an eccentric millionaire. Along with his wife, he's been building a mansion on a secluded island surrounded by a harsh and unforgiving sea. But when she disappears under mysterious circumstances, Emily Grace is hired to finish the project believe the house is cursed, but their warnings go unheeded as Emily Grace works to rebuild her life.After what she's been through, nothing can scare her--except perhaps the attention of a handsome man offering more than friendship. Andyet, there's something strange about this solitary fortress. Accidents. Mishaps. Ghostly whispers through the surrounding forest, footsteps when she's completely alone . . . Is there truly a curse or is the ethereal specter in the window an omen of something more sinister?"--